Crystallization and X‐ray diffraction analysis of the N‐terminal domain of the Toll‐like receptor signalling adaptor protein TRIF/TICAM‐1. Issue 7 (22nd July 2013) - Ullah, M. Obayed; Ve, Thomas; Dkhar, Jameris; Alaidarous, Mohammed; Ericsson, Daniel J.; Sweet, Matthew J.; Mansell, Ashley; Kobe, Bostjan
<x xml:space="preserve">Abstract</x> As part of the mammalian innate immune response, Toll‐like receptors 3 and 4 can signal via the adaptor protein TRIF/TICAM‐1 to elicit the production of type‐I interferons and cytokines. Recent studies have suggested an auto‐inhibitory role for the N‐terminal domain (NTD) of TRIF. This domain has no significant sequence similarity to proteins of known structure. In this paper, the crystallization and X‐ray diffraction analysis of TRIF‐NTD and its selenomethionine‐labelled mutant TRIF‐NTDA66M/L113M are reported. Thin plate‐like crystals of native TRIF‐NTD obtained using polyethylene glycol 3350 as precipitant diffracted X‐rays to 1.9 Å resolution. To facilitate phase determination, two additional methionines were incorporated into the protein at positions chosen based on the occurrence of methionines in TRIF homologues in different species. Crystals of the selenomethionine‐labelled protein were obtained under conditions similar to the wild‐type protein; these crystals diffracted X‐rays to 2.5 Å resolution. The TRIF‐NTD and TRIF‐NTDA66M/L113M crystals have the symmetry of space groups P212121 and P1, and most likely contain two and four molecules in the asymmetric unit, respectively. These results provide a sound foundation for the future structure determination of this novel domain.